Upper limb exercise for people on haemodialysis following arteriovenous fistula surgery - Termpong Reanpang (2019)
© 2019 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd. This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: This review aims to determine the best type of upper extremity exercise for AVF maturation (prior to and post AVF creation) in ESKD patients. The result will be applied to clinical practice to improve AVF outcome. This review also aims to define adverse events related to the upper extremity exercise.